Durable, Lightweight, Washable and Comfortable Cooling Textiles from Nanodiamond/Polydopamine/Wool Nanocomposites. Issue 5 (10th February 2022) - Rehman, Aisha; Houshyar, Shadi; Mirabedini, Azadeh; Cheng, Deshan; Cai, Guangming; Padhye, Rajiv; Wang, Xin
Abstract: The development of cooling textiles has a significant impact on energy saving and cost‐effectiveness in the context of global warming. Engineering textiles with cooling performance while maintaining their intrinsic traits, for example, lightweight, washable, comfort, and durability, is a great challenge in developing personal cooling garments. Here, the synthesis of nanodiamond/polydopamine/wool (ND‐PDA‐wool) nanocomposites through a facile dip‐coating approach is demonstrated. Different types of ND including detonation ND (DND), carboxylated ND (ND‐COOH) and hydroxylated ND (ND‐OH), are used, and dopamine templating is applied to achieve strong adhesion and bonding between fiber and ND. The morphology, structure, and properties of the as‐coated fabrics are characterized, and the cooling performance together with comfort are measured. Due to the excellent thermal conductivity of ND, the temperature difference between the coated fabrics and uncoated ones is around 2.4–3.9 °C within a short time span of 30 min. The coated ND‐PDA‐Wool fabrics demonstrated enhanced thermal stability and improved mechanical properties with excellent durability, and the water absorbency is greatly enhanced with well‐maintained air permeability. ND‐PDA‐wool composite fabrics offer a strategy to develop durable, lightweight, washable, and comfortable cooling textiles with immense potential in energy saving and reducing space cooling costs. Abstract : Nanodiamond/polydopamine/wool fiber (ND‐PDA‐wool) nanocomposites are synthesized through a facile dip‐coating approach for the development of cooling textiles. Due to the excellent thermal conductivity of ND, the temperature difference of 2.4–3.9 °C between the as‐coated wool fabrics and uncoated ones can be achieved within a short time span of 30 min.